A unique case of clear cell variant of calcifying epithelial odontogenic tumor involving the maxilla - Rudra Prasad Chatterjee; Swagata Gayen; Sanchita Kundu; Moumita Chattaraj; Mousumi Pal; Sanjeet Das (Wolters Kluwer Medknow Publications, 2017)
Calcifying epithelial odontogenic tumor (CEOT) is a rare, benign, odontogenic tumor arising from the odontogenic epithelium and accounts for approximately 1% of all odontogenic tumors. Clear cell variant of CEOT is a distinct entity and has more aggressive biological behavior and higher chances of recurrence. Here, we present a unique case of clear cell variant of CEOT involving the left side of the maxillary alveolus in a 73-year-old female patient with thorough clinical, radiological, and histological details.